The nutritional composition of the vegetable soybean (maodou) and its potential in combatting malnutrition - Agyenim-Boateng, Kwadwo Gyapong; Zhang, Shengrui; Zhang, Shibi; Khattak, Aimal Nawaz; Shaibu, Abdulwahab; Abdelghany, Ahmed M.; Qi, Jie; Azam, Muhammad; Ma, Caiyou; Feng, Yue; Feng, Huoyi; Liu, Yitian; et al. (Frontiers in Nutrition, 2023)
Global malnutrition continues to be a canker owing to poor eating habits and over-reliance on the major staple crops. Vegetable soybean (maodou) is gaining popularity globally as an affordable snack and vegetable. In this study, we profiled the nutritional composition of 12 soybean cultivars at the vegetable (R6 - R7) and mature (R8) stages. The results showed that 100 g of maodou contained 66.54% moisture, 13.49% protein, 7.81% fatty acids, 2.47% soluble sugar, abundant content of minerals, and micronutrients, including folate (460 μg FW) and carotenoids (3935.41 μg FW). Also, the isoflavone content of maodou ranged between 129.26 and 2359.35 μg/g FW. With regard to the recommended daily allowance, 100 g fresh weight of maodou can contribute 26.98%, 115.57%, and 11.60% of protein, folate, and zinc, respectively, and significant proportions of other nutrients including linoleic acid (21.16%), linolenic acid (42.96%), zinc (11.60%) and iron (18.01%). On dry weight basis, maodou has 2 - 6 folds higher contents of folate, tocopherol, and carotenoid than the mature soybean. Furthermore, RNA-seq analysis revealed that key biosynthesis enzymes of quality traits are differentially expressed during seed development and may contribute to variations in the content of quality traits at the vegetable and mature stages. Correlation analysis of quality traits at both stages revealed that protein only correlated positively with zinc at the vegetable stage but negatively correlated with total tocopherol and total fatty acid at the mature stage. Complex associations among folates, soluble sugar and isoflavones were also identified. This study provides insight into the nutritional contents of vegetable soybean and proves that maodou is critical to fulfilling the nutritional requirement of most countries.